Classification of Power Quality Events - An Inclusive Review. Issue 1 (April 2021) - Sharma, Bharat Bhushan; Singh, Kawal Preet; Patel, Alok; Banshwar, Anuj; Sharma, Naveen Kumar; Pathak, Mohit
Abstract: Power Quality is major issue that has led to large amount of research by the industry and academic experts. The increased uses of the electronics in electrical utilities have created a need of monitoring the power quality and provide the mitigation to enhance the performance of the electrical equipment. With advancement in technologies and availability of various online monitoring tools, it is very important to assess and review these technologies. The increased rate of research in this field is proven to be beneficial to the consumers. Customers are now able to request for better quality of service and making the Power Quality issue more important. This paper provide an inclusive review of various application of signal processing on power quality events, analysis of artificial intelligent techniques to classify the signals and optimization techniques for decision making. The paper also explores the upcoming opportunities for power quality classification and further improvement in terms of higher performance of the electrical equipment.